Production Process Scheduling Using the FCFS (First Come First Served) Method, at CV. Clean Industry Unit - abu bakar s (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2024)
CV. Unit Clean Industry, a household cleaning equipment manufacturer, faces significant production delays due to inefficient scheduling using the First Come First Served (FCFS) method, with 35% of orders delayed by 5–7 days in 2023. This study aims to evaluate the effectiveness of FCFS and identify root causes of delays, focusing on material shortages and machine maintenance issues. Using a mixed-method approach, primary data from interviews and observations were combined with secondary production records from November 2019 to April 2025. Critical Ratio (CR) analysis and comparative evaluation of FCFS against SPT, LPT, and EDD methods were conducted. Results showed FCFS achieved the shortest average completion time (10.75 days) and lowest average delay (4.5 days), despite minor utilization (44.18%) and work-in-process (2.26 jobs) disadvantages. The study concludes that FCFS remains effective for CV. Unit Clean Industry but recommends improving material supply chain and machine maintenance to further reduce delays.